Quantitative analysis of time-resolved RHEED during growth of vertical nanowires. Issue 9 (21st February 2020) - Jakob, Julian; Schroth, Philipp; Feigl, Ludwig; Hauck, Daniel; Pietsch, Ullrich; Baumbach, Tilo
Abstract : In situ RHEED enables a height-resolved determination of the crystal structure of vertical nanowires via self-shadowing and ensemble shadowing. Abstract : We present an approach for quantitative evaluation of time-resolved reflection high-energy electron diffraction (RHEED) intensity patterns measured during the growth of vertical, free-standing nanowires (NWs). The approach considers shadowing due to attenuation by absorption and extinction within the individual nanowires and estimates the time dependence of its influence on the RHEED signal of the nanowire ensemble as a function of instrumental RHEED parameters and the growth dynamics averaged over the nanowire ensemble. The developed RHEED simulation model takes into account the nanowire structure evolution related to essential growth aspects, such as axial growth, radial growth with tapering and facet growth, as well as so-called parasitic intergrowth on the substrate. It also considers the influence of the NW density, which turns out to be a sensitive parameter for the time-dependent interpretation of the intensity patterns. Finally, the application potential is demonstrated by evaluating experimental data obtained during molecular beam epitaxy (MBE) of self-catalysed GaAs nanowires. We demonstrate, how electron shadowing enables a time-resolved analysis of the crystal structure evolution at the top part of the growing NWs. The approach offers direct access to study growth dynamics of polytypism in nanowire ensembles at the growth front region under standard growth conditions.